About influences of different actions on spectra of impurity photoluminescence in GaAs - Litovchenko, N.M.; Prokhorovich, A.V.; Strilchuk, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Considered is the possibility to determine changes stimulated by external actions on a ratio between different luminescence center concentrations in GaAs crystals when using their photoluminescence spectra. It was shown that hard data on those changes can be obtained only by a detailed study of lux-brightness characteristics of impurity and inter-impurity bands of luminescence. Correlation changes of luminescence intensities of those bands indicate a variation of radiating centers concentration, if their dependence on excitation level in initial crystals and those subjected to external actions are the same.